Pemenuhan Hak Korban Tindak Pidana Kekerasan Seksual dikaitkan dengan UU TPKS - Muzayin, Andi Faizal; Pinandang, Catur Alam; Arumpuspita Rois, Diandra Kis (Dinasti Research, 2024)
Sexual violence is an act carried out through coercion that aims to fulfill the desires of the perpetrator regardless of the status of the relationship with the victim. Cases of sexual violence certainly have a negative effect on the victims. News about sexual crimes can easily be disseminated, especially since the world has entered the 4.0 era where all information can be easily disseminated using the internet and technology. So based on this, many of the victims are silent about the incident that happened to them because they are afraid that the negative impact will spread widely so that the victim will get ostracized in society. The purpose of this journal is to analyze the fulfillment of the rights of victims of crimes against sexual violence associated with the Law on Crimes of Sexual Violence. This journal method uses a qualitative type. The results of the analysis of this journal are that Law Number 12 of 2022 Articles 66-70 describes the rights of TPKS victims. Some of the rights of victims that are used as a scope include protecting victims from criminal prosecution, protecting against loss of access to politics, education, job transfers, and jobs, protecting victims from law enforcement officials if there is an act of demeaning officials, keeping the victim's identity confidential, protecting victims from violence or the perpetrator's threats, protection information is properly provided in accessing it, and provides protection facilities as well as information about victims' rights.